Characterization of Bamboo Based Carbon Powder Applicable for Fabrication of Low-Cost Counter Electrodes of Dye-Sensitized Solar Cells - Joshi, Prakash (Tribhuvan University Journal, 2018)
Low-cost carbon powder prepared by carbonization of bamboo wood was characterized by means of X-rays diffraction (XRD) and Raman spectroscopy. The structural analysis of the carbon powder shows that the material is the composite of amorphous and graphitic forms of carbon. Furthermore, the carbon powder was used as the counter electrode material of dye-sensitized solar cell (DSC) and the electric property of the bamboo carbon based counter electrode was investigated by obtaining current-voltage (I-V) curve of the DSC.